The Resource Curse - What Have We Learned from Two Decades of Intensive Research: Introduction to the Special Issue. Issue 2 (1st February 2017) - Papyrakis, Elissaios
A bstract: There has been increasing interest in the so-called 'resource curse', that is the tendency of resource-rich countries to underperform in several development outcomes. This has generated a mountain of (often contradictory) evidence leaving many floundering in the flood of information. This special issue compiles eight papers from some of the most prominent contributors to this literature, combining original research with critical reflection on the current stock of knowledge. The studies collectively emphasise the complexities and conditionalities of the 'curse' – its presence/intensity is largely context-specific, depending on the type of resources, socio-political institutions and linkages with the rest of the economy.